Cardiovascular risk factors, atherosclerosis and venous thromboembolism - The Tromsø study - Hald, Erin Mathiesen (UiT The Arctic University of Norway, 2014)
Paper 1, 2 and 4 of this thesis are not available in Munin: 1. Brækkan SK, Hald EM, Mathiesen EB, Njølstad I, Wilsgaard T, Rosendaal FR, Hansen JB: ‘Competing risk of atherosclerotic risk factors for arterial and venous thrombosis in a general population: the Tromsø study’. Arterioscler Thromb Vasc Biol., 2012 Feb;32(2):487-91. Available at http://dx.doi.org/10.1161/ATVBAHA.111.237545 2. Hald EM, Brækkan SK, Vik A, Brodin EE, Hansen JB: ‘Postprandial lipemia is not increased in patients with previous unprovoked venous thromboembolism’. J Clin Lipidol., 2013 Jan-Feb;7(1):48-55. Available at http://dx.doi.org/10.1016/j.jacl.2012.06.001 4. Hald EM, Lijfering WM, Mathiesen EB, Johnsen SH, Løchen ML, Njølstad I, Wilsgaard T, Rosendaal FR, Brækkan SK, Hansen JB: ‘Carotid atherosclerosis predicts future myocardial infarction but not venous thromboembolism: the Tromsø study’. Arterioscler Thromb Vasc Biol., 2014 Jan;34(1):226-30. Available at http://dx.doi.org/10.1161/ATVBAHA.113.302162 Venous thromboembolism (VTE) is a common and potentially fatal disease, often occuring in the absence of obvious predisposing factors. Recent observational studies in selected populations have suggested a closer association between arterial thrombosis (myocardial infarction (MI) and stroke) and VTE, two disease entities considered separate in terms of pathophysiology, epidemiology and treatments. The aim of this thesis was to investigate the relation between atherosclerosis, atherosclerotic risk factors and risk of incident VTE in a general population. We recruited study participants from the fourth survey of the Tromsø study, conducted in 1994-95. In this study, more than 27,000 men and women, aged 25-97 years, participated, and a subset of participants (n= 9056) were also invited to a more extensive second visit. Incident VTE events were registered from the date of inclusion until the end of follow up, and in papers 1 and 4, incident MI events were also registered. Furthermore, we performed a case-control study in which 20 ...